DESA PAKRAMAN SEBAGAI LEMBAGA ADAT DAN LEMBAGA AGAMA BAGI KEHIDUPAN MASYARAKAT HINDU DI BALI - Ida Bagus Putu Eka Suadnyana (Dharma Duta, 2020)
Desa Pakraman as a customary law community unit in Bali which has a unity of tradition and social life manners of the Hindu community has descended descendantly in the "Kahyangan Tiga" or "Kayangan Desa" that has a certain area and its own assets and has the right to manage its own household, of course, has a role which is very strategic in maintaining the customs and culture of Bali. We must support the large role carried by Desa Pakraman in various forms of reinforcement. Strengthening the existence of Desa Pakraman is not only from its institutions but also from various supporting fields. Given the enormous role of Desa Pakraman in the successful development of Balinese society. Desa Pakraman as the bearer of the main task in preserving Hindu cultural and religious values ​​in Bali needs to be maintained and fostered in line with developments in technology and the current modernization. In addition, Desa Pakraman also has the right to manage its own household. This means that the Desa Pakraman has full autonomy in carrying out the parhyangan, pawongan and palemahan based on awig-awig Desa Pakraman village and is technically operationally regulated by perarem.